Low-power wide-area network for Internet of things - Hamza, I. S.; Mnushka, O. V. (Харківський національний автомобільно-дорожній університет, 2018)
Experts predict a large increase in numbers of small electric devices for a next decade. This devices will be used in vide verity of areas of ours modern days life, and will allow people to have more control over environment. That creates need in figuring out a way to connect those devices rationally.
Keywords: 004.735